Understanding EFL Students’ Readiness for English Learning: Primary Teachers’ Perspectives in Indonesia’s Deep Learning Context - Salma Nadila; Sri Kusuma Ningsih (FOSTER: Journal of English Language Teaching, 2026)
The implementation of the deep learning approach in Indonesian primary education requires students to be adequately prepared to engage in meaningful and active learning experiences. Although previous studies have examined students’ readiness and teachers’ readiness separately, limited research has explored how primary school English teachers perceive students’ readiness for English learning within the deep learning context. This study investigated teachers’ perspectives on EFL students’ readiness and the factors influencing it in Indonesian primary schools. A qualitative case study was conducted involving four English teachers from public primary schools across four regions of Jakarta who had two to ten years of teaching experience and were actively teaching during the study. Data were collected through semi-structured interviews and classroom observations and analyzed using thematic analysis. The findings revealed that students’ readiness was influenced by prior knowledge, learning enthusiasm, and environmental support. However, anxiety, low motivation, and limited exposure to English often hindered their readiness. To address these challenges, teachers employed interactive learning media and collaborative activities to enhance students’ engagement, confidence, and participation. These findings contribute to a better understanding of students’ readiness within the deep learning framework and provide practical insights for English teachers, schools, and curriculum developers in supporting effective English learning at the primary level.